Assessment of Knowledge, Attitude, Practice, and Prevalence of Pediatric Medical Emergencies among Urban Dental Practitioners: A Cross-sectional Study - H. N. Subhadra; Indu Varkey; Jyotirmayee Dalai (Indian Journal of Dental Sciences)
Background: Pediatric medical emergencies require interventions beyond the usual scope of dental practice and can be potentially life-threatening. However, few studies have assessed the knowledge, attitude, practice, and prevalence of pediatric medical emergencies and its complications among dentists. Aim: This cross-sectional study aimed to assess the knowledge, attitude, practice, and prevalence of pediatric medical emergencies and its complications among urban dental practitioners. Materials and Methods: A prevalidated, semistructured, and close-ended questionnaire was distributed among 884 dentists with dental clinics or multispecialty dental setups in a metrocity and adjacent urban locality. The questionnaire comprised 64 questions pertaining to the following areas: Demographics, questions related to recording medical history, emergency drugs and equipment possessed by the practitioners, preparedness of staff, and dentist and prevalence of pediatric medical emergencies and complications. The comparisons among those who answered positively and negatively to the various questions, i.e., proportions (percentages/frequencies) of participants were done using the Chi-square test. Results: A total of 609 forms were evaluated. The highest percentage of practitioners (32.8%) have between 9 and 15 years of experience. The most number of emergency events recorded (5.12 cases per dentist) was in the group with 2–5 years of experience. All participants in the present study enquired about patients’ history, allergies, and their general health status. While 66.33% practitioners had <50% of the recommended emergency drugs, 48.4% of them stated that their office staff members were trained in handling emergency equipment, 74.4% could identify emergency drugs, but only (43.8%) had written protocols describing the staff member’s roles in the management of a medical emergency. Conclusion: Based on the results of the study, there is poor knowledge among practitioners about the management of pediatric medical emergencies across the metropolitan city and the adjacent urban locality. The self-assessed competence reflects an average level of competence among practitioners in dealing with various emergencies. In addition, a relatively lower prevalence of medical emergencies in pediatric patients was reported.